Neuroendocrine Differentiation Is a Prognostic Factor for Stage II Poorly Differentiated Colorectal Cancer. (28th June 2014) - Liu, Yue; Xu, Jinghong; Jiao, Yurong; Hu, Yeting; Yi, Chenghao; Li, Qiong; Tong, Zhou; Wang, Xiaowei; Hu, Lifeng; Xiao, Qian; Li, Jun; Ding, Kefeng
Abstract : Neuroendocrine differentiation (NED) in colorectal cancer is an indistinct phenomenon and may define a new cancer subtype, especially in the poorly differentiated colorectal cancer (PDCRC). The clinical features of PDCRC with NED remain controversial, thus confusing the implementation of individualized treatment. This study included 171 patients who underwent surgery from 2000 to 2011 and had pathology-confirmed PDCRC. Each sample was examined by immunohistochemistry for the biological markers of NED, synaptophysin (Syn), and chromogranin (CgA). Patients with Syn(+) and/or CgA(+) cells were classified as NED(+); otherwise, they were NED(−). Data were collected for patients who were followed up for at least two years. NED(+) staining was present in 71 (41.5%) patients. The median survival time was 36.9 months. No survival differences existed between the NED(−) and NED(+) groups ( P > 0.05 ) . However, stage II NED(+) patients had a significantly worse prognosis than NED(−) patients ( P = 0.018 ) . For the NED(+) group, the median survival was 38.56 months, and the 5-year survival was 65%. For the NED(−) group, the median survival was 53.18 months, and the 5-year survival was 90%. NED is a common event in primary PDCRC. For stage II PDCRC, NED(+) indicates a poor prognosis.